2007
DOI: 10.1300/j083v49n01_10
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating Relocation

Abstract: Most older adults prefer to live at home as long as possible, requiring supports and services to help them age in place. This study examines the relocation concerns of a group of older adults in a suburban naturally-occurring retirement community (NORC). Twenty-six percent of the 324 residents interviewed expressed concern about having to move in the next few years. Residents who were worried differed from those who did not worry on a number of demographic and biopsychosocial characteristics. Overall, resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…The lack of response is often attributed to the fact that transitions in functional status, care arrangements, and residential situations are potential stressors for individuals and families -- they are often associated with emotional upheaval and negative physical sequelae (Carpenter et al, 2007; Lafortune, Béland, Bergman, & Ankri, 2009; Pot, Deeg, Twisk, Beekman, & Zarit, 2005) -- but few long-term or large scale studies have been conducted to better understand the barriers to Preparation for Future Care (PFC)(Carpenter et al, 2007; Lafortune et al, 2009; Pot et al, 2005; Pot, Zarit, Twisk, & Townsend, 2005; Rossen & Knafl, 2007; Zimmer, Wen, & Kaneda, 2010). The purpose of this study is to introduce tools to further investigate factors that facilitate and prevent future care planning in larger samples and diverse populations, using an epidemiological approach.…”
Section: Assessing Future Care Preparation In Late Life: Two Short Mementioning
confidence: 99%
“…The lack of response is often attributed to the fact that transitions in functional status, care arrangements, and residential situations are potential stressors for individuals and families -- they are often associated with emotional upheaval and negative physical sequelae (Carpenter et al, 2007; Lafortune, Béland, Bergman, & Ankri, 2009; Pot, Deeg, Twisk, Beekman, & Zarit, 2005) -- but few long-term or large scale studies have been conducted to better understand the barriers to Preparation for Future Care (PFC)(Carpenter et al, 2007; Lafortune et al, 2009; Pot et al, 2005; Pot, Zarit, Twisk, & Townsend, 2005; Rossen & Knafl, 2007; Zimmer, Wen, & Kaneda, 2010). The purpose of this study is to introduce tools to further investigate factors that facilitate and prevent future care planning in larger samples and diverse populations, using an epidemiological approach.…”
Section: Assessing Future Care Preparation In Late Life: Two Short Mementioning
confidence: 99%
“…Everard, Lach, Fisher, and Baum (2000) reported a coefficients ³.71 for the four domains measured, and Carpenter et al (2007) reported a coefficients ³.83. Test-retest reliability has been reported as high, with intraclass correlations ranging from .71 (Carpenter et al, 2007) to .98 (Chan, Chung, & Packer, 2006). ACS scores have content, construct, and predictive validity (Baum & Edwards, 2008).…”
Section: Instrumentsmentioning
confidence: 99%
“…The notion of getting help is not pressing because the care demands still seem manageable. This is a good time for caregivers to learn about the disease, its treatment, care options, and other financial or legal matters (Carpenter et al, 2007). …”
Section: Preparation For Future Care In the Context Of Dementiamentioning
confidence: 99%